Zgledi iz osnov linearne algebre: Povzetek teorije in postopki reševanja nalog s komentarji - Kosi Ulbl, Irena (University of Maribor Press, 2022)
Examples from Bases of Linear Algebra: Theory Resume and Fully Solved Problems with Commentaries. The publication is a supplement to the textbook Bases of Linear Algebra (by the same author). At the beginning of each chapter, there is an introduction which foretells the problems that are going to be solved in this chapter. This is followed by a short theoretical part with written definitions, properties and theorems that we need when solving problems. The central part of the chapter is represented by examples solved in detail with all intermediate steps. Solving problems is also accompanied by comments that remind students which theoretical basis is used to find the solution. Each chapter ends with key words and the main findings of the chapter. In some examples, color pictures or various graphic displays help to make the solution process easier to understand and provide a better spatial representation.